SARS-CoV-2-specific antibody responses following BNT162b2 vaccination in individuals with multiple sclerosis receiving different disease-modifying treatments - Lambrianides, Anastasia; Deeba, Elie; Hadjiagapiou, Maria; Pantzaris, Marios; Krashias, George; Christodoulou, Christina (Frontiers in Neurology, 2023)
Introduction The study aims to evaluate the concentration of IgG antibodies against the receptor-binding domain of the SARS-CoV-2 spike1 protein (S1RBD) in BNT162b2- vaccinated relapsing-remitting multiple sclerosis (RRMS) individuals receiving disease-modifying treatments (DMTs). Methods Serum from 126 RRMS volunteers was collected 3 months after the administration of the second dose of the Pfizer-BioNTech BNT162b2 vaccine. Additional samples were analyzed after the administration of the booster dose in fingolimod- treated MS. Anti-S1RBD IgG antibody concentrations were quantified using the ABBOTT SARS-CoV-2 IgG II Quant assay. Results Anti-S1RBD IgG antibody concentrations in RRMS individuals receiving natalizumab, interferons, teriflunomide, and dimethyl fumarate showed no significant difference to those in healthy controls. However, fingolimod-treated MS individuals showed a marked inability to produce SARS-CoV-2- specific antibodies (p < 0.0001). Furthermore, a booster dose was not able to elicit the production of IgG antibodies in a large portion of matched individuals. Discussion A possible explanation for the altered immune response in fingolimod- treated MS individuals could be due to the medication inhibiting the circulation of lymphocytes, and possibly in turn inhibiting antibody production. Overall, patients on DMTs are generally of no disadvantage toward mounting an immune response against the vaccine. Nevertheless, further studies require evaluating non-humoral immunity against SARS-CoV-2 following vaccination, as well as the suitability of such vaccinations on patients treated with fingolimod.